ANALISIS KETIMPANGAN PEMBANGUNAN WILAYAH ANTAR PROVINSI (STUDI KASUS PULAU JAWA TAHUN 2014-2023) - Khairunnisa; Maryunani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Development is a multidimensional process involving transformations in social, economic, infrastructure, norms, and institutional fields with the primary goal of improving the standard of living of the people. One common issue found in the development process is the disparity that occurs due to high economic growth not being accompanied by equitable distribution. Java Island, with its superior contribution to the national economy and an economic growth rate that exceeds the national growth, is not exempt from experiencing development disparities. The purpose of this research is to analyze the variables suspected to influence development disparity in six (6) provinces in Java Island, namely DKI Jakarta, Banten, West Java, Central Java, Yogyakarta, and East Java for the years 2014-2023. The variables used are Foreign Direct Investment (FDI), Domestic Direct Investment (DDI), Human Development Index (HDI), capital expenditure, and economic growth. The research method employed is the Williamson Index and panel data regression. The research results indicate that the variable of capital expenditure has a positive effect and economic growth has a negative effect on development disparity. Meanwhile, FDI, DDI, and HDI do not affect development disparity.